The Effect of Using Fishbowl Strategy on Students’ Reading Comprehension - Jonri Kasdi; Muhammad Auzar (Lembaga penelitian dan pengabdian kepada masyrakat, 2016)
The objectives of the research were to find out the students’ reading comprehension of narrative text taught by using Fishbowl strategy, to find out the students’ reading comprehension of narrative text taught without using this strategy and to find out whether there was a significant effect of using Fishbowl strategy on students’ reading comprehension of narrative text at SMA N 3 Mandau. The design of this research was a quasi-experimental design. In collecting the data, the writer used both pre- and post- test to collect the data of the reading comprehension of narrative text of the first year students at state senior high school 3 Mandau.The number of sample from two classes was 87 students. In analyzing the data, the writer used an independent sample t-test. By using SPSS 22.0 and to was compared with ttable considering df. The writer concluded that there is a significant effect of using Fishbowl strategy on students’ reading comprehension of narrative text at State Senior High School 3 Mandau, where tobtained= 3.863 is higher than t-table either at 5%=2.00 or 1%=2.65